Extractive Spectrophotometric Estimation of Ambroxol - Reddy, M.N.; Murthy, T.K.; Srinivasu, K.; Latha, P.V.M.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Three simple and sensitive extractive spectrophotometric methods have been developed for the determination of ambroxol in pure and in its dosage forms. The developed methods involve formation of colored chloroform extractable complexes of drug with orange II, bromocresol green, bromophenol blue in acidic medium. Extractable complexes showed absorption maximum at 490 nm, 430 nm and 420 nm and showed linearity in concentration ranges of 5 to 40 μg/mL, 2.5 to 25 μg/mL and 5 to 40 μg/mL respectively. Results were validated statistically and were found to be reproducible.